TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG DISMENORE PADA SISWI KELAS X DI SEKOLAH MENENGAH KEJURUAN BATIK 1 SURAKARTA - Mursudarinah; Riski Aprilia; Nur Hikmah (Universitas Duta Bangsa Surakarta, 2022)
Introduction: Dysmenorrhea or menstrual pain is one of the most common gynecological complaints in young women who are in their teens. Menstrual pain is a symptom and not a disease. In Indonesia, the incidence of primary dysmenorrhea is 54.89% while the rest are secondary dysmenorrhea sufferers. In Central Java, 1.07%-1.31% of the number of sufferers of menstrual pain came to the obstetrics division. Objectives: This study aims to determine the level of knowledge of young women about dysmenorrhea in class X students at SMK Batik I Surakarta. Methods: in the form of a mini research with quantitative descriptive methodology and this research uses a probability sampling technique, namely proportionate stratified random sampling with a sample of 66 students of SMK Batik 1 Surakarta class X and uses univariate analysis and the instrument used is a questionnaire. Result: Primary data collection was carried out at SMK Batik 1 Surakarta with the results of a good level of knowledge, namely 19 people (28.8%), enough for 32 people (48.5%), less than 15 people (22.7%). Conclusion: The majority of young women's level of knowledge at SMK Batik 1 Surakarta about dysmenorrhea is sufficient. Teenagers are expected to always increase knowledge about dysmenorrhea in order to prevent or overcome the occurrence of dysmenorrhea.